Effect of Plyometric Jump Training on Skeletal Muscle Hypertrophy in Healthy Individuals: A Systematic Review With Multilevel Meta-Analysis - Arntz, F.; Mkaouer, B.; Markov, A.; Schoenfeld, B. J.; Moran, J.; Ramirez-Campillo, R.; Behrens, M.; Baumert, P.; Erskine, R. M.; Hauser, L.; Chaabene, H. (Frontiers in Physiology, 2022)
Objective: To examine the effect of plyometric jump training on skeletal muscle hypertrophy in healthy individuals. Methods: A systematic literature search was conducted in the databases PubMed, SPORTDiscus, Web of Science, and Cochrane Library up to September 2021. Results: Fifteen studies met inclusion criteria. The main overall finding (44 effect sizes across 15 clusters [median=2, range=1 to 15 effects per cluster) indicated that plyometric jump training had small to moderate effects (standardised mean difference [SMD]=0.47 [95%CIs=0.23 to 0.71]; p<0.001) on skeletal muscle hypertrophy. Subgroup analyses for training experience revealed trivial to large effects in non-athletes (SMD=0.55 [95%CIs=0.18 to 0.93]; p=0.007) and trivial to moderate effects in athletes (SMD=0.33 [95%CIs=0.16 to 0.51]; p=0.001). Regarding muscle groups, results showed moderate effects for the knee extensor (SMD=0.72 [95%CIs=0.66 to 0.78], p<0.001) and equivocal effects for the plantar flexor (SMD=0.65 [95%CIs=-0.25 to 1.55]; p=0.143). As to the assessment methods of skeletal muscle hypertrophy, findings indicated trivial-to-small effects for prediction equations (SMD=0.29 [95%CIs=0.16 to 0.42]; p<0.001) and moderate-to-large effects for ultrasound imaging (SMD=0.74 [95%CIs=0.59 to 0.89]; p<0.001). Meta-regression analysis indicated that the weekly session frequency moderates the effect of plyometric jump training on skeletal muscle hypertrophy, with a higher weekly session frequency inducing larger hypertrophic gains (β=0.3233 [95%CIs=0.2041 to 0.4425]; p<0.001). We found no clear evidence that age, sex, total training period, single session duration, or the number of jumps per week moderate the effect of plyometric jump training on skeletal muscle hypertrophy (β=-0.0133 to 0.0433 [95%CIs=-0.0387 to 0.1215]; p=0.101 to 0.751). Conclusion: Plyometric jump training can induce appreciable skeletal muscle hypertrophy, regardless of age and sex. There is evidence for relatively larger effects in non-athletes compared with athletes. Further, the weekly session frequency seems to moderate the effect of plyometric jump training on skeletal muscle hypertrophy, whereby more frequent weekly plyometric jump training sessions elicit larger hypertrophic adaptations.